Diamonds and Rust - Barash, Adi; Shatz, Ruthie (Israel, 2001)
On the trawler “The Spirit of Namibia,” moored off the coast of Namibia, diamond mining goes on around the clock. The supply of the coveted little diamonds on the ocean floor seems endless, but their extraction is muddied by politics, and fraught with racial tension. The directors received permission to film everyday life on “The Spirit of Namibia” from diamond exporter De Beers, but the result hardly flatters the company: white South Africans spouting racist theories and bad jokes, Cubans who write poetry and speak of love, an Israeli security manager who makes himself the enemy, and Namibian deck hands who find themselves colonized off the coast of their own country. While showing fraying tempers, racist attitudes, a deteriorating vessel and front office indifference “Diamons and Rust” takes us into the daily life of an international crew working in the service of a faceless mining conglomerate that controls not only the ship but the surrounding waters as well.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films